THE EFFECT OF MARITAL STATUS ON FEMALE LEADERSHIP ROLES AND ATTITUDES - Kőműves, Zsolt; Szabó, Szilvia; Szabó-Szentgróti, Gábor; Hollósy-Vadász, Gábor (Studia Mundi – Economica, 2022)
In this study, we examine the impact of marital status on leadership roles and attitudes for female leaders. In our study, we seek to answer the following research question: does marital status influence perceptions of leadership roles among female leaders? Three hypotheses are formulated: H(1): respondents perceive different factors as important for leadership success based on their marital status. H(2): respondents will consider different characteristics to be important for successful male leaders based on their marital status. H(3): respondents have different views on whether they would postpone starting a family in order to have a good job opportunity, based on their marital status. A questionnaire (n=225) was carried out. The sample is not representative therefore, our research results are not generalizable and the conclusions drawn are not considered valid outside the survey sample. The results were processed using ANOVA, Chi-squared tests. Our results confirmed all three hypotheses. Our results showed that women leaders differed in how they perceived the importance of reputation, household support, parental or kinship support, and friendship support in successful leadership. Respondents ranked different characteristics of successful male leaders according to their marital status. In the future, we would like to explore the differences between attitudes towards female and male leaders in a comparative study in a nationally representative survey.